Kalanchoe torrejacqii (Crassulaceae subfam. Kalanchooideae), a new species in K. subg. Bryophyllum from the Namorona River valley, Madagascar - Shtein, Ronen; Smith, Gideon F. (Phytotaxa, 2021)
Kalanchoe torrejacqii (Crassulaceae subfam. Kalanchooideae) is described as a new phyllo-bulbiliferous species. It occurs in the Namorona River valley, near Ranomafana, southern Madagascar. Differences between K. torrejacqii and the partially sympatric K. laxiflora are discussed and the new species is contrasted with representatives of the K. rosei complex with which it shares some similarities. Kalanchoe torrejacqii is the most northern pink-flowered species among other such species that belong to the recently described K. sect. Invasores, to which K. laxiflora and representatives of the K. rosei complex also belong.